2016
DOI: 10.1177/0962280213507506
|View full text |Cite
|
Sign up to set email alerts
|

Normalization of mean squared differences to measure agreement for continuous data

Abstract: Agreement among observations on two variables for reliability or validation purposes is usually assessed by the evaluation of the mean squared differences (MSD). Many transformations of MSD have been proposed to interpret and make statistical inferences about the agreement between the two variables, including the concordance correlation coefficient (CCC) and the random marginal agreement coefficient (RMAC). This paper presents a normalization of MSD based on a reference range and uses it to derive CCC and RMAC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“… is the PDF of the xj scores given examinee a's ability. This PDF can be obtained through the Lord and Wingersky (1984) recursion formula using which was employed by Almehrizi (2013;2016).…”
Section: The New Section-level Person Fit Statisticmentioning
confidence: 99%
“… is the PDF of the xj scores given examinee a's ability. This PDF can be obtained through the Lord and Wingersky (1984) recursion formula using which was employed by Almehrizi (2013;2016).…”
Section: The New Section-level Person Fit Statisticmentioning
confidence: 99%
“…The best matching position is found in the reference frame (usually the adjacent frame of the target frame) for each block. There are many measures of matching degree, including SAD (Sum of Absolute Differences) [ 29 ], MSD (Mean Square Differences) [ 30 ] and NCC (Normalized Cross Correlation) [ 31 ]. The best matching location search methods include FS (Full Search) [ 32 ], TSS (Three-Step Search), NTSS (New Three-Step Search) [ 33 ], and 4SS (Four-Step Search) [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Examples of scaled scores include percentile ranks, age equivalents, standardized scores, and normalized scores. Reliability of the aforementioned scores was investigated abundantly in previous research studies (e.g., Almehrizi, 2013Almehrizi, , 2016Brennan & Lee, 1999;Feldt & Qualls, 1998;Kolen & Lee., 2011;Kolen et al, 1992;Kolen et al, 2012;Lee, 2007) which concluded that there is a need for investigating the reliability of all types of test scaled scores besides the reliability of summed scores. The Standards for Educational and Psychological Testing (American Educational Research Association, American Psychological Association, & National Council of Measurement in Education, 2014) emphasize that reliability should be examined for all scores that are employed in test reports for better interpretation and utilization of test scores.…”
mentioning
confidence: 99%